OPTIMALISASI METODE PEMBELAJARAN PADA PENDIDIKAN AGAMA ISLAM BAGI ANAK TUNAGRAHITA - M. Isnando Tamrin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: In Islam, children are a mandate that must be maintained, regardless of the child's physical condition. They have the same rights as their parents, especially in terms of learning. What're more, children who are born with various needs, which are called children with special needs, such as mentally retarded children. Children who are born with intelligence that is significantly below the average are accompanied by an inability to adapt (Kustawan D, 2016). Children with mental retardation are also children who have academic barriers so that in their learning, modifications to the curriculum are needed by paying attention to the form of their special needs. However, even though in the reality of their lives they experience difficulties academically, this does not mean that they should also be neglected to get the religious learning they profess. They have the right to get proper religious learning and a place, whether they get it at home or in an educational institution (school). So that mentally retarded children have good gamma knowledge in their lives.Keywords: Learning Methods, Islamic Religious Education, Impairment.